Social and intelligent governance for the Municipal GAD of Tulcán - Quenguán Mavisoy , Kevin Javier (SATHIRI, 2022)
The present investigation, was proposed to study the organizational structure of the Autonomous Decentralized Municipal Government of Tulcán for the construction of a social and intelligent governance. In this sense, given the accelerated social and technological changes, it is essential that the municipal institution adopt new management models, to increase the levels of efficiency and effectiveness to improve the quality of life of citizens in a modern way. In such virtue, the structural organization of the Tulcaneño local government was based in a conceptual and theoretical way. On the other hand, it was pointed out that the dimensions of the social and intelligent governance model are applicable to the administrative functioning of the municipal institution. This was done through a qualitative methodology with a phenomenological and interpretive approach, which is based on knowing the subjective position of municipal officials. On the other hand, the objective of this work was to analyze the structural organization of the Municipal GAD of Tulcán for the construction of a social and intelligent governance. At the same time, the research question was: What conceptual elements allow us to know the functional structure of municipal governments? Finally, it can be established that at the organizational level the local government of Tulcán does allow the adoption of elements of the social and intelligent governance model. Thus, for example, the application of public value and the use of technology to improve the provision of public services.